A thematic analysis of Īqāẓ al-Himmam: Ibn ʿAjībah’s commentary on the Aphorisms (Ḥikam) of IbnʿAṭāʾAllāh - Jha, Sumit (2022)
This thesis thematically analyses Ibn ʿAjībah’s (d. 1224/1809) commentary on the Aphorisms (Ḥikam) of IbnʿAṭāʾAllāh (d. 709/1309), entitled Īqāẓ al-Himam fī Sharḥ al-Ḥikam (The Awakening of Spiritual Aspirations in the Commentary of the Ḥikam). The analysis uses Toshihiko Izutsu's methodology of semantic analysis to read and thematically parse the Īqāẓ before arranging the core thematic content under the analytic categories of teleology, ontology, soteriology and epistemology. Collectively these analytic categories encompass the notion of the ‘origin and the return’ (al-mabdaʾ wa al-maʿād), which is a comprehensive way of looking at the subject of spiritual wayfaring (sulūk). The thesis concludes by identifying the pivotal semantic phrase (focus word or phrase) that best serves as the overarching theme across the Īqāẓ and by extension across its source text, the Ḥikam. The thesis highlights this central theme as being ādāb al- maʿrifah (lit. the proprieties required of gnosis), that is, the propriety required to engender the experiential dimension of witnessing the One-ness of God (tawḥīd).